Evaluation Model of Character Education Programs in Islamic Religious Education and Moral Education Learning at SMP Negeri I Surakarta - Rismiyati Nurindarwati; Mulyoto Mulyoto; Dardiri Hasyim (Publikasi Indonesia, 2022)
The study aimed at describing the achievement of evaluation model of character education program in learning Islamic Religion and Attitude subject, in implementing teaching learning activity, extracurricular and implementing character education program in SMP Negeri 1 Surakarta. The study used CIPP (Contest, Input, Process, and Product) model as means to conduct evaluation. The approach used in this study was descriptive. The data were collected during evaluation process were by interview, observation, document and questionaire. The data were analyzed by using data reduction, data presentation, and drawing conclusion. The data sources were headmaster, committee, Islamic Religion teachers, students’ parents, and students of VIII and IX year. Result of the study showed that character education program in learning Islamic Religion and Attitude subject have achieved good result implemented by the school holder. On the stage of context, the mean achievement was 88.33% belonging to effective category. On the stage of input, it has achieved 91.78% belonging to effective category. On the stage of process, it has achieved 87.60% belonging to effective category. Finally, the stage of product showed the mean of 90.04% belonging to effective category. Overall, the implementation of character education program in learning Islamic Religion and Attitude subject has fulfilled the criterion standards, but there were several things to improve, such as: 1) headmaster in coordinating the activity together with the school holder needs to develop school activity to achieve excellent school, 2) teachers of Islamic Religion and Attitude use the whole competences in performing their duties as educator full of affection and improving character values in daily activity at school, 3) students in implementing their the character education values at school must be improved, 4) parents must give more attention for their children in educating and implementing habit in doing good behavior in daily life.